Social Capital and Health: Empirical Evidence from Indonesia - Rosalin, Cynthia (Makara Human Behavior Studies in Asia, 2018)
Through the Indonesian Family Life Survey (IFLS4 and IFLS5), this paper examined effects of individuals’ social capital on various health outcomes, analyzing specifically whether generalized trust, bridging social capital (trust in many ethnic groups, trust in many religious beliefs), and social isolation had effects on various health outcomes. Estimated results for fixed-effects models did not show significance in any health outcome variables, except for social isolation, which had a positive effect on self-perceived health. Moreover, estimated results for random-effect probit models showed that generalized trust had weak negative effect on self-perceived health, while trust in many ethnic groups had negative association. Meanwhile, trust in many religions had no effect on health outcomes. In addition, social isolation had negative effects on most self-rated health and mental health outcomes.